OPTIMALISASI TIGA PUSAT PENDIDIKAN MELALUI KURIKULUM TERSEMBUNYI DALAM PENGEMBANGAN KARAKTER AGAMA SISWA DI ASRAMA AL-AZHAR YOGYAKARTA - Ridho Agung Juwantara; Khusnul Khotimah (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2021)
The purpose of this study was to determine the strategic role of hidden curriculum in the process of instilling the value of character education through the contribution of school, family and community. This research is a qualitative research using a descriptive research approach. Data collection was carried out by making observations, in-depth interviews, documentation, and participation. The subjects of this study were board of dormitories and Ustadz or Ustadzah, student guardians, officials in the neighborhood of Al-Azhar Islamic boarding school and students. Data validity was checked by triangulating using different sources and methods. The results showed that; (1) The implementation of religious character education through the Hidden Curriculum in Al-Azhar Islamic Boarding School in Yogyakarta is carried out through; (a) Halaqoh: namely activities in the form of independent tadarus, language activities, guidance, guidance and supervision. (b) Outside the teachings of Halaqoh, namely Infaq Friday, dhuha prayer, a culture of clean living, a culture of discipline and 5S culture (smile, greetings, greetings, courtesy, and politeness). (2) Implementing the program to optimize the role of the three education centers in fostering religious character through; (a) integrating the values ​​of character education in boarding activities. (b) daily habituation. (3) The contribution of the three education centers in fostering religiosity through; (a) habitual formation method (habituation). (b) Training by applying examples. (c) Train with Wisdom. (d) committee meetings. (e) mosque-based activities (f) the community as stakeholders.